Mindfulness Creativity: Transforming stimulation methodology concept advertising process conception of the XXI Century - Vargas Delgado, José Jesús (Historia y Comunicación Social, 2014)
Our research is focused on the effects of an experimental study that examines in depth the discovery of a new stimulation paradigm conceptual methodological XXI Century: Mindfulness. The conventional analytical processes sequential stages to achieve the objectives of an individual primary creativity has always been tangentially materialized through a rational, rational creativity. A perspective study focused by perfectly rational variables allowed, predictably detect obvious deficiencies existed in the production process, and display the innovative emergence of the creative process from an emotional perspective, emotional creativity. The new paradigm of human development and its unique projection century environment, stimulates a conscious reformulation inspiring and transformative stage in the process of creation. Mindfulness Creativity. It is configured as a new methodology of personal growth stimulation transforms the basic axioms of creative production. Mindfulness is positioned as a sophisticated method that will find a way to calm and rescue the potential and value of advertising creations. Having overcome the sequential stages of life and creativity and empathy, we find a renewal stage fully oriented awareness creation on the present. Remove the automatic creative behaviors by increasing awareness of creative stimulation. Empty prejudices and value judgments, avoiding that stand in the productive capacity and potential for creative effectiveness. Open and available in new creative perspectives. Resilience creative and stimulating potential element that has the individual capacity to face adversity advertising creation environments. The aim of the paper is positioned to develop inferences and conclusions major qualitative and quantitative method in a transformer linked to conscious creativity mindfulness, which passes through the pursuit of a silence in the mind of creative, enabling it to reach a potential ability to hear clearly advertising intuition needed in the new educational paradigm century.
Keywords: Mindfulness; rational creativity; emotional creativity; midfulness creativity and creative mind.